Cardiovascular and pulmonary physical therapy : evidence to practice - 4 0 16; (Elizabeth W.) Frownfelter, Donna L.;Dean, Elizabeth; 5 (St. Louis, Mo. : Elsevier/Mosby, 2012)
Providing a solid foundation in cardiovascular and pulmonary physiology and rehabilitation, Cardiovascular and Pulmonary Physical Therapy: Evidence and Practice, 5th Edition uses the latest scientific literature and research in covering anatomy and physiology, assessment, and interventions. A holistic approach addresses the full spectrum of cardiovascular and pulmonary physical therapy from acute to chronic conditions, starting with care of the stable patient and progressing to management of the more complex, unstable patient. Both primary and secondary cardiovascular and pulmonary disorders are covered. In this edition, updates include new, full-color clinical photographs and the most current coverage of techniques and trends in cardiopulmonary physical therapy. Edited by Donna Frownfelter and Elizabeth Dean, recognized leaders in cardiovascular and pulmonary rehabilitation, this resource is ideal for clinicals and for practice.--Publisher's website.
Part I: Cardiovascular and Pulmonary Function in Health and Disease. Epidemiology as a Basis for Informing Contemporary Physical Therapy Practice ; Oxygen Transport: The Basis of Cardiovascular and Pulmonary Physical Therapy ; Cardiovascular and Pulmonary Anatomy ; Cardiovascular and Pulmonary Physiology ; Cardiovascular and Pulmonary Pathophysiology ; Cardiovascular and Pulmonary Manifestations of Systemic Conditions. -- Part II: Cardiovascular and Pulmonary Physical Therapy: Cardiopulmonary Assessment. Measurement and Documentation ; History ; Pulmonary Function Tests ; Arterial Blood Gases ; Imaging of the Chest ; Electrocardiogram Identification ; Multisystem Assessment and Laboratory Investigations ; Special Tests ; Clinical Assessment of the Cardiovascular and Pulmonary Systems ; Monitoring Systems, Catheters, and Devices in the Intensive Care Unit. -- Part III: Cardiovascular and Pulmonary Physical Therapy: Interventions. Maximizing Outcomes: Relating Interventions to an Individual's Needs ; Mobilization and Exercise: Physiologic Bases for Assessment, Evaluation and Training NEW! ; Mobilization and Exercise: Testing and Training NEW! ; Body Positioning ; Physiological Basis for Airway Clearance Techniques ; Airway Clearance Interventions ; Facilitating Ventilation Patterns and Breathing Strategies ; Exercise Testing and Training: Primary Cardiovascular and Pulmonary Dysfunction ; Exercise Testing and Training: Secondary Cardiovascular and Pulmonary Dysfunction ; Respiratory Muscle Training ; Complementary Therapies as Cardiovascular and Pulmonary Physical Therapy Interventions ; Patient Education. -- Part IV: Cardiovascular and Pulmonary Physical Therapy: Guidelines for the Delivery of Cardiovascular and Pulmonary Physical Therapy Acute Conditions. Individuals with Acute Medical Conditions ; Individuals with Acute Surgical Conditions. -- Part V: Cardiovascular and Pulmonary Physical Therapy: Guidelines for the Delivery of Cardiovascular and Pulmonary Physical Therapy Chronic Conditions. Individuals with Chronic Primary Cardiovascular and Pulmonary Dysfunction ; Individuals with Chronic Secondary Cardiovascular and Pulmonary Dysfunction. -- Part VI: Cardiovascular and Pulmonary Physical Therapy: Guidelines for the Delivery of Cardiovascular and Pulmonary Physical Therapy CriticalIntensive Care. Comprehensive Management of Individuals in the Intensive Care Unit ; Intensive Care Management of Individuals with Primary Cardiovascular and Pulmonary Dysfunction ; Intensive Care Management of Individuals with Secondary Cardiovascular and Pulmonary Dysfunction ; Intensive Care Management of Medical and Surgical Complications. -- Part VII: Cardiovascular and Pulmonary Physical Therapy: Guidelines for the Delivery of Cardiovascular and Pulmonary Physical Therapy Special Cases. The Neonatal and Pediatric Patient ; The Aging Patient ; The Patient with Multisystem Impairments Affecting Breathing Mechanics and Motor Control ; The Transplant Patient ; The Patient in the Community. -- Part VIII: Related Aspects of Cardiovascular and Pulmonary Physical Therapy. Body Mechanics: The Art of Positioning and Moving Patients ; Respiratory Care Practice Review ; Care of the Patient with an Artificial Airway ; Respiratory and Cardiovascular Drug Actions.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Diseases;Physical therapy.;rehabilitation.;rehabilitation.;therapy.;therapy. -- ardiopulmonary system;Lung Diseases;Physical Therapy Modalities.;Cardiovascular Diseases;Cardiovascular Diseases;Lung Diseases;Respiratory Therapy. -- 20; 20; 2